If x^2 + 3x + c = (x + a)(x + b) for all x, what is the : DS Archive
Check GMAT Club App Tracker for the Latest School Decision Releases http://gmatclub.com/AppTrack

It is currently 10 Dec 2016, 09:09
GMAT Club Tests

Close

GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track
Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

Close

Request Expert Reply

Events & Promotions

Events & Promotions in June
Open Detailed Calendar

If x^2 + 3x + c = (x + a)(x + b) for all x, what is the

  post reply Question banks Downloads My Bookmarks Reviews Important topics  
Author Message
Senior Manager
Senior Manager
avatar
Joined: 19 May 2004
Posts: 291
Followers: 1

Kudos [?]: 15 [0], given: 0

If x^2 + 3x + c = (x + a)(x + b) for all x, what is the [#permalink]

Show Tags

New post 30 Nov 2004, 12:12
00:00
A
B
C
D
E

Difficulty:

(N/A)

Question Stats:

0% (00:00) correct 0% (00:00) wrong based on 0 sessions

HideShow timer Statistics

This topic is locked. If you want to discuss this question please re-post it in the respective forum.

If x^2 + 3x + c = (x + a)(x + b) for all x, what is the value of c ?

(1) a = 1

(2) b = 2
Director
Director
User avatar
Joined: 07 Nov 2004
Posts: 689
Followers: 6

Kudos [?]: 142 [0], given: 0

 [#permalink]

Show Tags

New post 30 Nov 2004, 12:26
D

x^2 + 3x + c = (x + a)(x + b)
= x^2+ax+bx+ab

=> (a+b)x =3x ; c =ab

s[1]: a=1; b=3-a=2 => c=2
S[2]: b=2; a=3-2 =1 => c=2
Director
Director
User avatar
Joined: 31 Aug 2004
Posts: 610
Followers: 3

Kudos [?]: 118 [0], given: 0

 [#permalink]

Show Tags

New post 30 Nov 2004, 13:03
Another great one Dookie !

Nothing to add, D it is.
Senior Manager
Senior Manager
avatar
Joined: 19 May 2004
Posts: 291
Followers: 1

Kudos [?]: 15 [0], given: 0

 [#permalink]

Show Tags

New post 30 Nov 2004, 13:11
Yeah, i liked this question because at first, i wasn't sure that it's ok to go from:
(a+b)x+ab = 3x + c
To
=> (a+b)x =3x ; c =ab.

But then i realized that it must be correct, since both describe ONE specific line.

And there can only be one linear equation for this line.
:idea:
Intern
Intern
avatar
Joined: 04 Oct 2004
Posts: 10
Followers: 0

Kudos [?]: 0 [0], given: 0

 [#permalink]

Show Tags

New post 30 Nov 2004, 14:47
Is the OA D ?
Since c = ab => we need stmt 1 and stmt 2 to get c
Intern
Intern
avatar
Joined: 10 Nov 2004
Posts: 44
Followers: 1

Kudos [?]: 0 [0], given: 0

 [#permalink]

Show Tags

New post 02 Dec 2004, 05:41
we know that
x^2+(a+b)x+ab= (x+a)(x+b)
so it is D
_________________

I am not going to give up!!!

CIO
CIO
User avatar
Joined: 09 Mar 2003
Posts: 463
Followers: 2

Kudos [?]: 56 [0], given: 0

 [#permalink]

Show Tags

New post 03 Dec 2004, 07:58
Dookie wrote:
Yeah, i liked this question because at first, i wasn't sure that it's ok to go from:
(a+b)x+ab = 3x + c
To
=> (a+b)x =3x ; c =ab.

But then i realized that it must be correct, since both describe ONE specific line.

And there can only be one linear equation for this line.
:idea:


Hey Dookie,

This one is easier then you made it. Here's what I always teach my students:

whenever you've got this polynomial situation, there are always four elements to figure out. It'll always look like:

x^2 + bx + c = (x + d)(x + e).

And we always know that d + e = b and de = c

And of course we know how to factor the first to make the second if we have b and c, and we know how to mulitply the second to make the first if we've got d + e.

So the point is, we have enough informaiton as long as we have any two of b, c, d, and e to always get the other two. It's an absolute. Give me any two of those numbers, I'll give you the other two.

So in any problem, just look for two of them, and you'll get the other ones. You don't have to think about it - just do it.

Check out these example from the OG to back that up:

MC195
MC333
DS124
  [#permalink] 03 Dec 2004, 07:58
Display posts from previous: Sort by

If x^2 + 3x + c = (x + a)(x + b) for all x, what is the

  post reply Question banks Downloads My Bookmarks Reviews Important topics  


GMAT Club MBA Forum Home| About| Terms and Conditions| GMAT Club Rules| Contact| Sitemap

Powered by phpBB © phpBB Group and phpBB SEO

Kindly note that the GMAT® test is a registered trademark of the Graduate Management Admission Council®, and this site has neither been reviewed nor endorsed by GMAC®.